The elves and the shoemaker - Morgan, Hawys (London York press, 2020)
The shoemaker can't make any shoes. he hasn't got any money. he is sad and he goes to bed. the elves are nice ant they like making shoes. what does the shoemaker find in the morning?
English stories
1
Keywords: English stories